Serotonin 2A Receptor Agonist Binding in the Human Brain with [11C]Cimbi-36. Issue 7 (July 2014) - Ettrup, Anders; da Cunha-Bang, Sophie; McMahon, Brenda; Lehel, Szabolcs; Dyssegaard, Agnete; Skibsted, Anine W; Jørgensen, Louise M; Hansen, Martin; Baandrup, Anders O; Bache, Søren; Svarer, Claus; Kristensen, Jesper L; et al.
[ 11 C]Cimbi-36 was recently developed as a selective serotonin 2A (5-HT2A ) receptor agonist radioligand for positron emission tomography (PET) brain imaging. Such an agonist PET radioligand may provide a novel, and more functional, measure of the serotonergic system and agonist binding is more likely than antagonist binding to reflect 5-HT levels in vivo. Here, we show data from a first-in-human clinical trial with [ 11 C]Cimbi-36. In 29 healthy volunteers, we found high brain uptake and distribution according to 5-HT2A receptors with [ 11 C]Cimbi-36 PET. The two-tissue compartment model using arterial input measurements provided the most optimal quantification of cerebral [ 11 C]Cimbi-36 binding. Reference tissue modeling was feasible as it induced a negative but predictable bias in [ 11 C]Cimbi-36 PET outcome measures. In five subjects, pretreatment with the 5-HT2A receptor antagonist ketanserin before a second PET scan significantly decreased [ 11 C]Cimbi-36 binding in all cortical regions with no effects in cerebellum. These results confirm that [ 11 C]Cimbi-36 binding is selective for 5-HT2A receptors in the cerebral cortex and that cerebellum is an appropriate reference tissue for quantification of 5-HT2A receptors in the human brain. Thus, we here describe [ 11 C]Cimbi-36 as the first agonist PET radioligand to successfully image and quantify 5-HT2A receptors in the human brain.